Chapter 6. Population Sub-Structure and Management - Santos, Jorge (Septentrio Educational, 2015)
This chapter of CONΣERV IT deals with the following questions in aquatic conservation: - Does it matter how fish populations are divided spatially? - How do we deal with different spatial linkages, configurations and populations sizes in fisheries management? - How much biomass or money do we lose by not fishing or by over-fishing small and large mixed populations? ConservArea I Mainland_Island whelk macro ConservArea II Metapopulation sardine macro ConservArea III Stepping-stone salmon macro